Variability in Antithrombotic Therapy Regimens Peri-TAVR: A Single Academic Center Experience. Issue 2 (December 2015) - Rossi, Jeffrey; Noll, Andrew; Bergmark, Brian; McCabe, James; Nemer, David; Okada, David; Vasudevan, Anant; Davidson, Michael; Welt, Frederick; Eisenhauer, Andrew; Shah, Pinak; Giugliano, Robert
Abstract Introduction The aim of this study was to describe peri-procedural antithrombotic use in patients undergoing transcatheter aortic valve replacement (TAVR) at a single academic medical center. Methods Retrospective collection of antiplatelet and anticoagulant use during the index hospitalization for all patients undergoing TAVR at our institution from April 2009 through March 2014. Results Of a total of 255 patients undergoing the procedure, 132 (51%) had an indication for anticoagulation pre-TAVR and 92 (70% of those with an indication) were on treatment. On discharge, 106 patients (44% of total surviving to discharge, 73% of those surviving with an indication for anticoagulation) were treated with oral anticoagulation. Of these patients, 89 (84%) were discharged on aspirin and an oral anticoagulant without clopidogrel. Only 122 (51% of total patients) were discharged on the regimen of aspirin and clopidogrel alone. Conclusion Peri-procedural antithrombotic regimens vary greatly following TAVR. More than half of patients have an indication for anticoagulation following the procedure. Most patients at our institution who require anticoagulation are discharged on aspirin and an oral anticoagulant, though the optimal regimen requires further investigation.